2018
DOI: 10.1111/rec.12880
|View full text |Cite
|
Sign up to set email alerts
|

Major bottlenecks for the restoration of natural forests in Chile

Abstract: International agreements combined with the recent Chilean Forestry Policy (2015-2035) represent a challenge and an opportunity for forest landscape restoration in Chile. Nevertheless, restoring over 500,000 ha using mainly native species seems like a daunting task by 2035. Here, we discuss the three major bottlenecks that currently constrain the restoration efforts of forest ecosystems in Chile. First, Chile urgently needs a national strategic plan for forest landscape restoration, which should take into accou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
13

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 35 publications
0
30
0
13
Order By: Relevance
“…The bottlenecks identified by Bannister et al () are real threats to restoration programs for forest and non‐forest ecosystems in Chile, as well as elsewhere. However, issues related to seed sourcing, seed quality/availability, processing and storing seeds, dormancy‐breaking, and germination also severely limit the efficacy of active ecological restoration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bottlenecks identified by Bannister et al () are real threats to restoration programs for forest and non‐forest ecosystems in Chile, as well as elsewhere. However, issues related to seed sourcing, seed quality/availability, processing and storing seeds, dormancy‐breaking, and germination also severely limit the efficacy of active ecological restoration.…”
Section: Discussionmentioning
confidence: 99%
“…Bannister et al () identified three major bottlenecks for successful ecological restoration of Chilean forests, including “lack of a national plan for forest landscape restoration, poor quality and low supply of native plant species, and poor results in the establishment phase.” We agree with these three crucial barriers and offer a fourth, equally important bottleneck: lack of an adequate seed supply chain (Merritt et al ). The success of restoration plantings pivots on the entire set of practices along the chain of seed use, from seed collection to the point at which seedlings are delivered to field sites for outplanting (Merritt et al ).…”
Section: Introductionmentioning
confidence: 99%
“…One of the main bottlenecks for forest restoration is inadequate supply of native plant material. Lack of seeds (Jalonen et al, 2018; León‐Lobos et al, 2020; Merritt & Dixon, 2011) and planting stock (Bannister et al, 2018; Whittet et al, 2016) of target species from appropriate sources in the required amounts are often critically limiting. This problem is particularly acute in the tropics, where many tree species produce seeds that are difficult to store (i.e.…”
Section: The 10 Golden Rulesmentioning
confidence: 99%
“…Native ecosystems and their species distributions within the Chilean Mediterranean climate are not exempt from the effects of climate change related to increased drought (Garreaud et al, 2017). This has led to the development of restoration programs in ecosystems with high ecologic value (Bannister et al, 2018). Because knowledge concerning patterns of genetic variability in Chilean native species is scarce, the use of local plant material for restoration has been the customary approach.…”
Section: Introductionmentioning
confidence: 99%